2008
DOI: 10.1088/0031-8949/77/4/045002
|View full text |Cite
|
Sign up to set email alerts
|

Soliton excitation in the DNA double helix

Abstract: We study the nonlinear dynamics of the DNA double-helical chain using the Peyrard-Bishop-Dauxois (PBD) model. By using the Fourier series approach, we have found that the DNA dynamics in this case is governed by the modified discrete nonlinear Schrödinger (MDNLS) equation. Through the Jacobian elliptic function method, we investigate a set of exact solutions of this model. These solutions include the Jacobian periodic solution as well as bubble solitons. The stability of these solutions is also studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 57 publications
2
28
0
2
Order By: Relevance
“…The PBD model was also confirmed to be consistent with the formation of temporary sequencedependent openings observed by S1 nuclease cleavage experiments and with a multistep melting envisaged by experiments in heterogeneous DNA [23]. Some works have shown that the PBD model supports nonlinear local excitations [11,12,[24][25][26]. A few years ago, Joyeux and Buyukdagli [27] proposed a new dynamical model (JB model) for DNA, which is closer to the statistical ones than the PBD model.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…The PBD model was also confirmed to be consistent with the formation of temporary sequencedependent openings observed by S1 nuclease cleavage experiments and with a multistep melting envisaged by experiments in heterogeneous DNA [23]. Some works have shown that the PBD model supports nonlinear local excitations [11,12,[24][25][26]. A few years ago, Joyeux and Buyukdagli [27] proposed a new dynamical model (JB model) for DNA, which is closer to the statistical ones than the PBD model.…”
Section: Introductionsupporting
confidence: 75%
“…DNA plays a vital role in all living organisms since it is the key molecule responsible for duplication, storage, and realization of genetic information [11]. DNA is basically a complex structure containing two strands of linear polymers of residues (nucleotides), where each strand is made up of sugars, purine [adenine (A) and guanine (G)] and pyrimidine [cytosine (C) and thymine (T)] bases, and phosphates [12].…”
Section: Introductionmentioning
confidence: 99%
“…Evidently, the base-pairs can only de-naturate when the double helix is largely uncoiled and therefore we use a small angle [32,33]. One also consider the anharmonic Hamiltonian [34,35], where the same torsion angle dependence is introduced as in Equation 3 for the stacking interaction, (…”
Section: Brief Presentation Of the Twisted Dna With Solvent Interactionmentioning
confidence: 99%
“…Among them, we have the tanh-function method [41], the elliptic function approach [42], and the Hirota'sbilinearization method [29][30][31][32], to name just few. Here, the Hirota'sbilinearization method is used to investigate exact solitons solution of the PB model.…”
Section: Model and Mathematical Backgroundmentioning
confidence: 99%